Asymmetric localized states at a nonlinear interface of fractional systems with optical lattices - Zhou, Shu; Zeng, Jianhua; Qin, Yali (Frontiers in Physics, 2023)
We investigate the existence and stability of localized gap states at a nonlinear interface of nonlinear fractional systems in a one-dimensional photonic lattice. By using the direct numerical simulations and linear stability analysis, we obtain the stability of the asymmetric localized gap states in the first and second finite gaps. Our theoretical results show that the power of the localized gap states decrease gradually as the increase of propagation constant and the nonlinear landscape (nonlinear coefficient ratio between the left and right interface), providing insights into soliton physics in nonlinear periodic systems with fractional-order diffraction.